Secret data sharing using steganography and image processing - Bhuvanya, R; Vijayalakshmi, K; Uma, S; A.Suresh, A (International Journal of Engineering and Technology, 2018)
Steganography is a technique that helps to hide the secret data inside the digitally covered image. The message to be hidden can be a text,image, speech, video. The proposed method aims to combine the technique of steganography and Image Processing. Cover image helps to carry the secret data in an embedded form which is referred as stego image. This work proposes a new implementation process called clustering modification directions (CMDs). To implement this methodology, several sub images will be created by decomposing the cover image using additive distortion functions. To enhance the security, password protection is also applied for the hidden information to be retrieved.
Keywords: Stegnography; Image Processing; Clustering Modification Directions.